Auricular composite tissue graft for the correction of alar rim defect in Asian patients: a retrospective case series of 15 patients - Feng, Xinyi; Yu, Baofu; Wu, Qifeng; He, Jinguang; Zhou, Qimin; Yan, Yangxuanyu; Wei, Jiao; Dai, Chuanchang (Frontiers in Medicine, 2026)
BackgroundVarious procedures can now be utilized for the correction of alar rim defect, most notably alar rim grafts and local flap transplantation. However, each of these procedures possesses inherent limitations. In this retrospective case series, we present a novel approach using auricular composite tissue grafting for the treatment of alar rim defect.MethodsA retrospective analysis was conducted on 15 patients who underwent auricular composite tissue grafting. The surgical procedure included incision, release of nasal alar mucosa surrounding the alar rim, and subsequently harvest and transplantation of composite tissue from the antihelix region to the defect area. Surgical outcomes were assessed by standardized photographic measurements of alar height and a previously validated patient satisfaction questionnaire.ResultsNo postoperative local necrosis, infection, or delayed wound healing occurred in any patients. Three patients underwent secondary surgery to achieve an enhanced aesthetic results. Mild contraction and scar color mismatch were observed at 3–6 months after the operation. By 1 year, the scars were almost indistinguishable. During long-term follow-up, two patients presented mild retraction of the graft. Overall, 87% of the patients were satisfied with the outcome of the surgery.ConclusionAuricular composite tissue grafting appears to be a feasible technique for the repair of alar rim deformities, providing satisfactory aesthetic outcomes and high patient satisfaction.